Design of Study Program Performance Dashboard using Streamlit - Ilham, Moch Ilham A; Siswanto, Teddy; Sugiarto, Dedy (Intelmatics, 2024)
To achieve certain performance goals, such as increasing the integration of study program performance data from various sources, such as student data, lecturers, curriculum, research, and so on, a performance dashboard is needed to monitor the performance of lecturers, students and curriculum to be more efficient. In this study, a dashboard was created with streamlit where the data was taken from the web scraping method. By utilizing the data visualization capabilities owned by Streamlit, study program performance information can be presented in the form of graphs, diagrams, or tables that are easier to understand and interpret.